2016
DOI: 10.1055/s-0036-1593361
|View full text |Cite
|
Sign up to set email alerts
|

The Varus–Valgus Constrained Knee Implant: Survivorship and Outcomes

Abstract: The purpose of this study was to estimate the survivorship of the varus-valgus constrained (VVC) knee implants in primary, aseptic, and septic revision total knee arthroplasty (TKA); determine functional outcomes; main modes of failure; and variables associated with increased mechanical failures. In this study, 685 consecutive cases of primary ( = 247), aseptic ( = 315), and septic revision ( = 123) TKAs with VVC implants were performed between 1999 and 2008; 533 knees (78%) had a mean follow-up of 8.2 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Despite the disadvantages that have been associated with increased constraint, midterm survivorship from revision for aseptic loosening was 100%, which is in line with previous studies of primary CCK that reported no cases of failure of the implants for aseptic loosening at midterm follow-up in primary TKA [13,14,17,19,23,31,33]. Our results compare favorably with those of other studies [11,15,22,[34][35][36][37] (Table 3). No complications related to the tibial post mechanism were reported at a mean follow-up of 9 years (range 6-12 years).…”
Section: Discussionsupporting
confidence: 90%
“…Despite the disadvantages that have been associated with increased constraint, midterm survivorship from revision for aseptic loosening was 100%, which is in line with previous studies of primary CCK that reported no cases of failure of the implants for aseptic loosening at midterm follow-up in primary TKA [13,14,17,19,23,31,33]. Our results compare favorably with those of other studies [11,15,22,[34][35][36][37] (Table 3). No complications related to the tibial post mechanism were reported at a mean follow-up of 9 years (range 6-12 years).…”
Section: Discussionsupporting
confidence: 90%
“…The survival rates of the prostheses in this study were better than those in earlier reports and were comparable to those in recent reports. The failure rate for the VVC prosthesis used in the primary TKAs ranged from 0 to 22%, 20,26,27 and the rate ranged from 0 to 35.7% for revisions. 22,27,28 In the only study that has reported the outcomes of two-stage revision using the VVC implant, Wilke et al 22 reported a case with 71% overall 5-year survival and an estimated 64% 10-year survival when repeat revision surgery was used as the end point.…”
Section: Discussionmentioning
confidence: 99%
“…Hossain et al, 2019 [11] >5 mm excursion and mismatch in medial and lateral gaps in flexion, extension, or both; >15 valgus-varus laxity; gap mismatch that may predispose to cam dislocation with PS implant 38 without femoral stem: Stryker TS Johnson Jr et al, 2019 [13] Inadequately balanced or incompetent collateral ligament 20 with femoral stem: TCIII; 1 without femoral stem: TCIII Moussa et al, 2017 [9] Not discussed 354 without femoral stem: Exactech Optetrak Moussa et al, 2017 [9] Not discussed 85 with femoral stem: Zimmer, DePuy, Smith & Nephew, Exactech Siqueira et al, 2017 [12] Severe knee deformities, coronal instability, and failure to balance with less constrained implant [33] Surgeon judgment for CCK vs PS 55 without femoral stem: Exactech nonmodular Easley et al, 2000 [34] Genu valgum and MCL incompetence 28 with femoral stem: Zimmer CCK Hartford et al, 1998 [4] MCL insufficiency, severe valgus, and bone loss 17 with femoral stem: nonmodular and modular Zimmer CCK Font-Rodriguez et al, 1997 [35] Not discussed Specific implant not listed Lachiewicz and Falatyn, 1996 [5] Fixed flexion deformity (7), severe valgus (8), combined flexion and valgus deformity (7), MCL incompetence (2), post-traumatic (1)…”
Section: Appendix Appendixmentioning
confidence: 99%